Immunohistochemical Detection of Motor Endplates in the Long-Term Denervated Muscle - Mu, Liancai; Chen, Jingming; Li, Jing; Nyirenda, Themba; Fowkes, Mary; Sobotka, Stanislaw (Journal of Reconstructive Microsurgery, 2018)
Background We have demonstrated that the native motor zone (NMZ) within a muscle is an ideal target for performing nerve-muscle-endplate band grafting (NMEG) to restore motor function of a denervated muscle. This study was designed to determine spatiotemporal alterations of the myofibers, motor endplates (MEPs), and axons in the NMZ of long-term denervated muscles for exploring if NMEG-NMZ technique would have the potential for delayed reinnervation.Methods Sternomastoid (SM) muscles of adult female Sprague-Dawley rats (n = 21) were experimentally denervated and denervation-induced changes in muscle weight, myofiber size, MEPs, and intramuscular nerve axons were evaluated histomorphometrically and immunohistochemically at the end of 3, 6, and 9 months after denervation. The values obtained from the ipsilateral normal side served as control.Results The denervated SM muscles exhibited a progressive reduction in muscle weight (38%, 31%, and 19% of the control) and fiber diameter (52%, 40%, and 28% of the control) for 3-, 6-, and 9-month denervation, respectively. The denervated MEPs were still detectable even 9 months after denervation. The mean number of the denervated MEPs was 79%, 65%, and 43% of the control in the 3-, 6-, and 9-month denervated SM, respectively. Degenerated axons in the denervated muscles became fragmented.Conclusions Persistence of MEPs in the long-term denervated SM suggests that some surgeries targeting the MEPs such as NMEG-NMZ technique should be effective for delayed reinnervation. However, more work is needed to develop strategies for preservation of muscle mass and MEPs after denervation.
Keywords: denervation; peripheral nerve injury; motor endplate; acetylcholine receptor; muscle atrophy; native motor zone